2018
DOI: 10.3892/mmr.2018.8760
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits invasion and migration of colon cancer cells by recovering WIF1 expression

Abstract: Colon cancer is characterized by invasion and migration. DNA methylation of CpG islands in tumor suppressor genes is considered to be an epigenetic mechanism underlying cancer development. Epigenetic silencing of a gene may be reversed by drugs, including genistein. The present study aimed to determine the effect of genistein on Wnt inhibitory factor 1 (WIF1) and invasion, and migration of colon cancer cells. The viability of HT29 colon cancer cells was suppressed by genistein in a dose dependent manner. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…NF-κB is induced by irradiation and is shown to promote proliferation through the activation of c-myc, which is a negative regulator of p21, p27, and GADD45a [52,53]. Genistein has also been shown to inhibit expression of NF-κB and c-myc [54][55][56]. Genistein may be promoting cell cycle arrest by activating ERβ and thereafter inactivating NF-κB or directly inducing expression of cell cycle checkpoints.…”
Section: Mechanism Of Action: Pharmacologymentioning
confidence: 99%
“…NF-κB is induced by irradiation and is shown to promote proliferation through the activation of c-myc, which is a negative regulator of p21, p27, and GADD45a [52,53]. Genistein has also been shown to inhibit expression of NF-κB and c-myc [54][55][56]. Genistein may be promoting cell cycle arrest by activating ERβ and thereafter inactivating NF-κB or directly inducing expression of cell cycle checkpoints.…”
Section: Mechanism Of Action: Pharmacologymentioning
confidence: 99%
“…Genistein, a soybean‐derived isoflavonoid compound, has been shown to have health benefits effects on diverse cell functions . Numerous studies have shown that genistein‐induced antitumor activities through antioxidant, anti‐proliferation, the inactivation of MAPK pathway, induction cancer cell apoptosis, anti‐migration, inactivated glucose transporters (GLUT1), and Hexokinase 2 (HK2) to suppress aerobic glycolysis, induced estrogenic activity as an estrogen receptor agonist and down‐regulating thioredoxin‐1 in human hepatocellular carcinoma SNU‐449 cells . Genistein induces caspase‐independent apoptosis through inhibition of the NF‐κB pathway in T‐cell leukemia cells .…”
Section: Introductionmentioning
confidence: 99%
“…Genistein interacts with the catalytic domain of DNMT1, competing with hemi-methylated DNA for the catalytic pocket [ 120 ]. Furthermore, in colon cancer cells, genistein demethylated WIF1 and decreased invasiveness and migration of cancer cells by reducing expression of matrix metalloproteinases 2 and 9 [ 121 ]. Curcumin, a polyphenol compound with anti-inflammatory properties, also influences methylation status.…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%